2012
DOI: 10.3928/01477447-20111122-40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lumbar Disk Herniation on the Careers of Professional Baseball Players

Abstract: Outcomes after lumbar disk herniation in baseball athletes are currently unknown. It has been postulated that the repetitive torque-producing motions of a baseball player may have negative implications after a disk injury. Sixty-nine lumbar disk herniations (40 treated operatively, 29 nonoperatively) in 64 professional baseball players were identified, and important outcome measures including successful return to play, time to recovery, career longevity, and performance based on vital statistics to each positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 16 publications
2
52
0
1
Order By: Relevance
“…For NHL players, Schroeder et al [17] reported an average of 129.6 hockey games played postoperatively. For MLB players, the average career longevity postoperatively was 232.8 games, as reported by Earhart et al [8]. For NFL players, the average postoperative career longevity was 36 games [9].…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…For NHL players, Schroeder et al [17] reported an average of 129.6 hockey games played postoperatively. For MLB players, the average career longevity postoperatively was 232.8 games, as reported by Earhart et al [8]. For NFL players, the average postoperative career longevity was 36 games [9].…”
Section: Resultssupporting
confidence: 68%
“…The average reported recovery time for athletes undergoing lumbar discectomy to return to active play ranged from 2.8 to 8.7 months [8,23,24,29]. The shortest reported recovery time was 2 months for a professional ballerina (n = 1) [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations